Glial maturation factor-β deficiency prevents oestrogen deficiency-induced bone loss by remodelling the actin network to suppress adipogenesis of bone marrow mesenchymal stem cells - Jun Xu; Zhongyue Huang; Si Shi; Jiangni Xia; Guangnan Chen; Kaifeng Zhou; Yiming Zhang; Chong Bian; Yuqin Shen; Xiaofan Yin; Lixia Lu; Huijie Gu (Cell Death and Disease)
Abstract An imbalance between the adipogenesis and osteogenesis of bone marrow mesenchymal stem cells (BMSCs) is considered the basic pathogenesis of osteoporosis. Although actin cytoskeleton remodelling plays a crucial role in the differentiation of BMSCs, the role of actin cytoskeleton remodelling in the adipogenesis of BMSCs and postmenopausal osteoporosis (PMOP) has remained elusive. Glia maturation factor-beta (GMFB) has a unique role in remodelling the polymerization/depolymerization cycles of actin. We observed that GMFB expression was increased in bone tissue from both ovariectomized (OVX) rats and PMOP patients. GMFB knockout inhibited the accumulation of bone marrow adipocytes and increased bone mass in the OVX rat model. The inhibition of adipocyte differentiation in GMFB knockout BMSCs was mediated via actin cytoskeleton remodelling and the Ca2+-calcineurin-NFATc2 axis. Furthermore, we found that GMFB shRNA treatment in vivo had favourable effects on osteoporosis induced by OVX. Together, these findings suggest a pathological association of the GMFB with PMOP and highlight the potential of the GMFB as a therapeutic target for osteoporosis patients.